Exploring Teachers' Challenges and Effective Strategies in Teaching English Reading Skills to Autistic Learners in Pakistan - Shehreen Ibrahim; Qasim, Muhammad (Journal of Education and Learning Environments, 2026)
In this qualitative study, the authors examine the problems and methods adopted by the English language teachers who are teaching autistic Pakistani students. In recognition of the unique cognitive, communicative, and behavioural patterns of learners with Autism Spectrum Disorder (ASD), the study investigates teacher navigation in inclusive education in resource-limited settings. The focus of the in-depth interviews was to use a phenomenological method that would interrogate six teachers of both public and private schools in Karachi. Key challenges, such as the shortage of autism-specific training, behavioural issues management, communication barriers, inflexible curriculum, and insufficient institutional support, were revealed through thematic analysis. It was notwithstanding these constraints that the teachers showed ingenuity and adapted methods like visual aids, simplified content instructions, phonics-based learning, and one-on-one classes. These were effective strategies, though mostly informal and self-generated, since formal training or systemic guidance was not provided. The results highlight the urgent necessity to provide specific training to teachers, invest in infrastructure, and supply resources. This paper will add to the body of knowledge concerning special needs education in Pakistan, and teachers will play a pivotal role in ensuring access and inclusion of English reading methods among autistic students.